Twinning during recrystallization and its correlation with the deformation microstructure. (October 2022) - Lin, Fengxiang; Zhang, Yubin; Godfrey, Andrew; Juul Jensen, Dorte
Abstract: The formation of annealing twins during recrystallization in a cold-rolled copper single crystal has been studied. A new method is proposed to classify annealing twins according to their orientation relationship with the surrounding deformed matrix. A statistical analysis based on the new classification method shows that during growth of a recrystallized grain, twinning occurs more frequently on twinning planes close to one of the 111 planes of the deformation microstructure, and most frequently when the 111 plane is the dominant slip plane of the deformed matrix for the present single crystal. The differences in morphology for different types of twins are discussed based on growth selection criteria. The study highlights the importance of the local deformation microstructure on the formation of annealing twins . Graphical abstract: Image, graphical abstract